2022
DOI: 10.1002/nop2.1447
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of supportive relationships between child‐bearing women and midwives

Abstract: Aims To review and evaluate the literature on the factors related to developing supportive relationships between women and midwives, including facilitators and barriers. Design An integrative review. Method The search used CINAHL, MEDLINE, Embase, EMcare, Maternity and Infant Care, PsycINFO, and Google Scholar from January 2009–June 2020. Two reviewers screened the eligible studies, and 2,399 records were identified. Quality was assessed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The results of this research are in line with previous research that women can build good relationships with peers or midwives and can get information from various experiences and what can be done by midwives (15). Organizational factors, such as staffing ratios and workload issues, may impede midwives' abilities to build supportive relationships with women (16).…”
Section: Process In Implementing Pregnancy Classessupporting
confidence: 85%
“…The results of this research are in line with previous research that women can build good relationships with peers or midwives and can get information from various experiences and what can be done by midwives (15). Organizational factors, such as staffing ratios and workload issues, may impede midwives' abilities to build supportive relationships with women (16).…”
Section: Process In Implementing Pregnancy Classessupporting
confidence: 85%
“…Antenatal care in the UK follows the midwife-led model of care, where the organisation of care from booking in to delivery is built around a partnership between midwife and women [36]. This care is based on a supportive and trusting relationship between midwives and the women in their care [37]. Many women in this study reported positive experiences of their antenatal care, but many also reported more negative aspects of care.…”
Section: Antenatal Care Is Inconsistentmentioning
confidence: 88%
“…Training in intrapartum counseling skills is essential for registered midwives to effectively provide emotional support and promote the health of women and their babies [21]. Although the Better Births Initiative (BBI) standards advocate for a doula or companionship in labor as an evidence-based intervention, the current study revealed that the majority of registered midwives did not recommend women to have their doulas during labor and childbirth [23]. This finding is consistent with another study that noted a lack of encouragement from midwives with respect to the presence of a doula and the integration of cultural and personal preferences during childbirth [24].…”
Section: Evaluation Of Midwifery Practicesmentioning
confidence: 91%
“…A study examining the experiences of male registered nurses undergoing clinical training in midwifery at a regional hospital in the Eastern Cape discovered that these nurses perceived midwifery as anxiety-inducing, daunting, and diminishing their confidence [22]. On the contrary, the women who participated in these studies were found to exhibit less anxiety, as midwifery is traditionally viewed as a feminine domain [23]. The results revealed that a minority of the respondents had advanced midwifery specialization, while few had basic midwifery qualifications.…”
Section: Demographic Information Of Registered Midwivesmentioning
confidence: 99%